Zika virus in Brazil and the danger of infestation by Aedes (Stegomyia) mosquitoes - Marcondes,Carlos Brisola (2016)
Abstract Zika virus, already widely distributed in Africa and Asia, was recently reported in two Northeastern Brazilian: State of Bahia and State of Rio Grande do Norte, and one Southeastern: State of São Paulo. This finding adds a potentially noxious virus to a list of several other viruses that are widely transmitted by Aedes (Stegomyia) aegypti and Aedes (Stegomyia) albopictus in Brazil. The pathology and epidemiology, including the distribution and vectors associated with Zika virus, are reviewed. This review is focused on viruses transmitted by Aedes (Stegomyia) mosquitoes, including dengue, Chikungunya, Zika, Mayaro, and yellow fever virus, to emphasize the risks of occurrence for these arboviruses in Brazil and neighboring countries. Other species of Aedes (Stegomyia) are discussed, emphasizing their involvement in arbovirus transmission and the possibility of adaptation to environments modified by human activities and introduction in Brazil.